A role for legitimacy metrics in advancing and sustaining environmental water reforms?. Issue 1 (2nd January 2019) - Marshall, Graham R.; Lobry De Bruyn, Lisa A.
ABSTRACT: Legitimacy deficits have been identified as central to the ongoing challenges encountered in implementing the policy reforms introduced to reduce the environmental impacts of over-allocating water in the Murray-Darling Basin. In closing the special issue on Building and Maintaining Trust and Legitimacy in Environmental Water Management, this article draws on the preceding articles in responding to a call for the focus of evaluations of environmental water reforms to be broadened to assess their performance against metrics of legitimacy. The first aim is to consider some analytical issues to be encountered in developing legitimacy metrics for MDB environmental water reform contexts. The other aim is to explore the role of legitimacy metrics in empirical research designed to strengthen the evidence available for deciding whether and how to invest in establishing and sustaining the legitimacy of the MDB reforms. Particular reference is made to empirical studies of the consequences and antecedents of legitimacy in U.S. contexts of the law and its policing. Furnishing policy makers with reliable evidence to guide their decisions on whether and how to invest in the legitimacy of the MDB environmental water reforms will require studies of this kind that are adapted to the unique contexts of these reforms.